Sistem Cerdas untuk Optimalisasi Kelayakan Pemberian Diskon kepada Customer BerbasisWeb Programming dengan Pendekatan Smart Method - Oktavittho Angkhosho; Teti Desyani (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
Business competition in the Food & Beverages (F&B) industry, particularly cafes, is highly competitive, requiring business owners to implement effective marketing strategies to maintain customer loyalty. Café Kovilla in South Tangerang faces this challenge, where discount offerings are still subjective, incidental, and do not optimally utilize customer transaction data.This research aims to design and build a web-based intelligent system as a Decision Support System (DSS) to optimize the discount eligibility process. The system development method used is Research and Development (R&D), with the Simple Multi-Attribute Rating Technique (SMART) approach as the core of decision-making. The system’s feasibility was evaluated using Black Box Testing, White Box testing, and User Acceptance Test (UAT). The results show the system was successfully built and is functional, covering the management of alternatives, criteria, and automated ranking calculations. The SMART method proved effective in ranking customers. Black Box testing results showed all functionalities were VALID, and White Box testing on the login function with a Cyclomatic Complexity of 3 also passed. UAT testing on 20 respondents yielded a feasibility percentage of 87%, falling into the “Very Good”category. The system is concluded to be feasible for implementation to support more objective, data-driven decision-making at Café Kovilla.